Health for the 21st century: myth or reality - Yábar V., Edgard (2020)
In October of last year, the national health situation was exposed in which the know that at least 4 million Peruvians do not have some type of health coverage (El Peruvian, 2020, para. 2). This text was developed in the last two years as a reflection on the complex dilemma that is the health and well-being of our people. At this juncture of 2020, the government proposes as an annual development slogan the phase: "Year of the universalization of health", with the aim of providing health insurance for all Peruvians. For this reason, this essay highlights the path that the concept of health in our country has evolved in recent decades.